Cytomegalovirus-Associated Severe Fatal Necrotizing Pancreatitis in a Patient with Interstitial Pneumonitis Treated with Steroids. An Autopsy Case - Terada, Tadashi (JOP. Journal of the Pancreas, 2011)
Context An autopsy case of cytomegalovirus (CMV) associated with fatal severe pancreatitis is reported. Case report A 76-year-old man presented with high fever and was admitted to our hospital for evaluation. Imaging modalities, including chest X-ray, CT and MRI, revealed interstitial pneumonia. Blood laboratory tests showed positive anti-nuclear antigen (x80), but collagen diseases were not identified. The patient was treated with steroids (prednisolone 30 mg/day). Two months later, the patient developed acute abdominal pain. Serum laboratory tests revealed an elevated amylase level (1,296 IU/L), and CT demonstrated acute pancreatitis. The patient died of multiple organ failure from the acute pancreatitis three days after the onset of the acute pancreatitis. An autopsy revealed severe necrotizing acute pancreatitis. Numerous large inclusions of CMV were found in the acinar and ductal cells of the pancreas. Numerous CMV inclusions were also seen in the degenerated and necrotic pancreatic acinar cells. CMV-infected cells were immunohistochemically positive for CMV antigen, CMV early antigen and CMV late antigen, indicating active replication and regression of CMV. Conclusion The findings strongly suggest that severe CMV infection can occur after steroid administration, and that CMV infection can be the cause of severe fatal acute necrotizing pancreatitis. Image: The lungs show intestinal pneumonitis.